2011
DOI: 10.7705/biomedica.v31i4.450
|View full text |Cite
|
Sign up to set email alerts
|

Los cirujanos sobreestiman el riesgo de malignidad de los nódulos tiroideos, evaluación de los estimados subjetivos usando un análisis bayesiano

Abstract: Introduction: Thyroid nodules are the most common endocrine condition treated by surgeons. The main purpose of the evaluation of a thyroid nodule is to rule out a carcinoma. Medical decisions concerning thyroid nodules are highly influenced by subjective beliefs. Objective: To assess the subjective probabilities of malignancy that are assigned to the clinical characteristics of a patient with a thyroid nodule in order to determine the degree of influence that these probabilities have on the final clinical susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similarly, Lee et al found that observer variability between two physicians diagnosing TNs using US images varied with their experience [ 6 ]. In certain cases, high subjectivity can lead to an overestimation or underestimation of the risk for malignancy of nodules [ 7 ]. Seifert et al in their study discussed the subjectivity in TN classification among different physicians using various TIRADS classification methodologies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lee et al found that observer variability between two physicians diagnosing TNs using US images varied with their experience [ 6 ]. In certain cases, high subjectivity can lead to an overestimation or underestimation of the risk for malignancy of nodules [ 7 ]. Seifert et al in their study discussed the subjectivity in TN classification among different physicians using various TIRADS classification methodologies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%